2020
DOI: 10.3390/molecules25235544
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Tioconazole and Melaleuca alternifolia Essential Oil Pickering Emulsions for Onychomycosis Topical Treatment

Abstract: Onychomycosis is a disease that affects many adults, whose treatment includes both oral and topical therapies with low cure rates. The topical therapy is less effective but causes fewer side effects. This is why the development of an effective, easy to apply formulation for topical treatment is of high importance. We have used a nanotechnological approach to formulate Pickering emulsions (PEs) with well-defined properties to achieve site-specific delivery for antifungal drug combination of tioconazole and Mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Combination included: azoles or terbinafine or griseofulvin plus plant extracts including essential oils (19/30 studies), azoles or terbinafine or amorolfine plus immunosuppressant agents (3 studies), azoles or terbinafine plus peptides (3 studies), azoles plus disinfectants (3 studies), and other combinations including antifungal agents plus efflux pump inhibitors and statins. Checkerboard titration methodology was the most common procedure for testing the combination, followed by agar methods (i.e., disk diffusion and agar dilution) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combination included: azoles or terbinafine or griseofulvin plus plant extracts including essential oils (19/30 studies), azoles or terbinafine or amorolfine plus immunosuppressant agents (3 studies), azoles or terbinafine plus peptides (3 studies), azoles plus disinfectants (3 studies), and other combinations including antifungal agents plus efflux pump inhibitors and statins. Checkerboard titration methodology was the most common procedure for testing the combination, followed by agar methods (i.e., disk diffusion and agar dilution) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…They act in two ways: by neutralizing free radicals (the antioxidant effect) and as anti-inflammatory agents by inhibiting the release of pro-inflammatory mediators. Secondary metabolites produced by plants are also capable of acting in a third way, as antifungal agents [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. A synergistic interaction between antifungal agents and natural products was often seen ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, a nanotechnological approach was applied to formulate PEs in combination with azole derivative (tioconazole) and Melaleuca alternifolia EO tested against C. albicans and T. rubrum . The findings showed that PEs are an excellent choice for onychomycosis topical treatment compared to conventional emulsions or ethanolic solutions of reference drugs [ 145 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 30 mL of sterile SDA was added in one Petri dish (90 mm × 15 mm) and kept for solidifying to yield a thickness of 6 mm. Trichophyton mentagrophyte (ATCC 24953) suspension was cultured on potato dextrose agar medium and incubated at 28 °C for 10 days as described previously [ 42 ]. SDA plates were inoculated by placing a sterile cotton-tipped applicator in a suspension containing spores (1.0 × 10 6 CFU/mL) and spreading it over the plate surface and being permitted to dry for 15 min.…”
Section: Methodsmentioning
confidence: 99%